The Effectiveness of Village Fund Allocation in Improving Farmers’ Welfare in Deli Serdang - Rahmad Sembiring; Annisa Ilmi Faried; Lia Nazliana Nasution; Dina Mariana Pasaribu (Jurnal Ilmiah Akuntansi Kesatuan, 2026)
This study examines the effectiveness of village fund allocation as an instrument for advancing the economic welfare of agricultural households in Deli Serdang Regency, North Sumatra Province, over the period 2019 to 2024. Using a quantitative research framework and secondary data, this study builds a multivariable regression model that includes community participation, institutional capacity, agricultural infrastructure spending, and village fund allocation as the main predictors of farmers’ welfare outcomes. With an adjusted R-squared of 0.591, the dependent variable, the farmers’ welfare index, shows a moderate but statistically significant response to all four independent factors. Despite consistent year-on-year increases in village fund disbursements from IDR 156.4 billion in 2019 to IDR 228.9 billion in 2024, the farmer exchange rate only surpassed the benchmark threshold of 100 from 2022 onward, indicating a structural lag between fiscal input and welfare output. The study concludes that strengthening institutional governance, redirecting a greater proportion of allocations toward productive agricultural empowerment programs, and institutionalizing participatory planning mechanisms are necessary preconditions for maximizing the developmental impact of village funds on farming communities.